Direct measurement of Nb3Sn filament loading strain and stress in accelerator magnet coil segments. (6th March 2019) - Scheuerlein, C; Wolf, F; Lorentzon, M; Hofmann, M
Abstract: We have directly measured, for the first time, the Nb3 Sn and Cu loading strains and stresses in 11 T dipole coil segments upon compressive loading using neutron diffraction. For this purpose a load frame that enables rotation of the sample load axis with respect to the neutron scattering geometry was installed in the Stress-Spec beamline at the Heinz Maier-Leibnitz FRM II neutron source. The neutron diffraction data suggests that the magnet coil wound of Rutherford type cables can be considered as a fibre reinforced composite material. In the axial load direction the load is mainly carried by the Nb3 Sn filaments and the composite stiffness can be estimated by the rule of mixtures assuming iso-strain conditions in all composite constituents. Under transverse compression the fully annealed Cu provides an isotropic pressure around the Nb3 Sn filaments. The transverse load stresses in the Cu and Nb3 Sn are similar, indicating iso-stress behaviour of the coil constituents under transverse compression. The broadening of the Nb3 Sn diffraction peaks above critical stress values indicates reversible and irreversible Nb3 Sn loading stress effects.